Anti-progressive collapse behavior of beam-to-column assemblies with bolted-angle connections under different span ratios. Issue 6 (April 2018) - Meng, Bao; Zhong, Weihui; Hao, Jiping
This article discusses the anti-progressive collapse performance of three specimens, with top-seat angles with double web-angle connections, under different span ratios. Double full-span assemblies extracted from steel frames with a typical column-removal scenario were designed and applied in a monotonic static loading experiment. The failure modes/sequences, strain, internal force conditions, and the transformed law of the resistance mechanism are examined. The results obtained show that specimens with equal spans can provide greater resistance due to full development of flexural and catenary actions. For specimens with unequal spans, the catenary resistance from the short beam portion is larger than that from the long beam portion, and the asymmetry of the span is not beneficial to the structure's bearing capacity in preventing progressive collapse. The three specimens' dynamic increase factors are also discussed in terms of the energy balance principle and their development trend for nonlinear static analysis related to catenary action.